Influence of thickness on ethanol sensing characteristics of doctor-bladed thick film from flame-made ZnO nanoparticles - Liewhiran C. (2014)
ZnO nanoparticles were produced by flame spray pyrolysis (FSP) using zinc naphthenate as a precursor dissolved in toluene/acetonitrile (80/20 vol%). The particle properties were analyzed by XRD, BET, and HR-TEM. The sensing films were produced by mixing the particles into an organic paste composed of terpineol and ethyl cellulose as a vehicle binder and were fabricated by doctor-blade technique with various thicknesses (5, 10, 15 μm). The morphology of the sensing films was analyzed by SEM and EDS analyses. The gas sensing characteristics to ethanol (25-250 ppm) were evaluated as a function of film thickness at 400°C in dry air. The relationship between thickness and ethanol sensing characteristics of ZnO thick film on A12O3 substrate interdigitated with Au electrodes were investigated. The effects of film thickness, as well as the cracking phenomenon, though, many cracks were observed for thicker sensing films. Crack widths increased with increasing film thickness. The film thickness, cracking and ethanol concentration have significant effect on the sensing characteristics. The sensing characteristics with various thicknesses were compared, showing the tendency of the sensitivity to ethanol decreased with increasing film thickness and response time. The relationship between gas sensing properties and film thickness was discussed on the basis of diffusively and reactivity of the gases inside the oxide films. The thinnest sensing film (5 μm) showed the highest sensitivity and the fastest response time (within seconds). © 2007 by MDPI.